A Cloud-Native Test Automation Framework For Secure Ott Content Delivery Systems (International Journal of Environmental Sciences, 2025)
The current paper outlines a cloud-native, automated testing framework dedicated to the purpose of supporting safe distribution of OTT (Over-the Top) media content with the help of Digital Rights Management (DRM) systems. The demand of streaming services has been burning intensely and the content protection schemes and mechanisms have been becoming too sophisticated to handle, but at the same time, ensuring a secure playback across a heterogeneous device type has become an important and a difficult task. The architecture that was proposed combines real-device, UI, API and continuous integration and Continuous Delivery (CI/CD) pipelines built on Kubernetes and containerized microservices. The framework encompasses DRM compliance, content playback integrity and platform compatibility by virtue of setting up the DRM method through automated orchestration and parallel testing, and embedded security validation all at scale. Tests and trials reveal that the system has the capability of carrying out more than 1000 simultaneous DRM tests with success rates that are overwhelming and minimal latency. The CI/CD lifecycle integration of security audit evidenced over 85 percent decrease in the number of exposures in vulnerability upon adoption of the framework. Moreover, cross-platform compatibility of mobile, web, and smart TVs, using real-device playback verification, was also initiated because of the low ratio of buffer rate and crash. The findings prove the efficiency of the framework as the scalable, secure and performance-efficient mode of the contemporary OTT content delivery systems. The method is very scalable and can be used in edge-based streaming and AI-based content protection in future.